Influences of Corporate Governance, Independent Directors, Shareholders’ Meeting Quality a - Suppaporn, Uaychai; Dampitakse, Kusuma (Journal of Humanities and Social Sciences, Rajapruk University, 2022)
This study aims to investigate the influence of corporate governance, independent committee, shareholder meeting quality, and cash flow from operating activities on the earnings quality of listed companies on The Stock Exchange of Thailand SET 100 group. Data was collected from the Company’s financial statements, annual report, Stock Market’s Supervision Report, and the results of the announcement of project scores assessment of the quality of shareholders’ meetings from 2017 to 2019. The statistics used for data analysis were descriptive statistics including maximum, minimum, mean, and standard deviation, and Inferential statistics using multiple regression analysis. The results revealed that Independent Board Proportion and cash flows from operating activities had a positive influence on earnings quality. In addition, it found that no significant influence of corporate governance assessment and the assessment of the quality of the shareholders’ meeting on earnings quality.